2016
DOI: 10.21037/jgo.2016.06.09
|View full text |Cite
|
Sign up to set email alerts
|

EGFR family and cMet expression profiles and prognostic significance in esophagogastric adenocarcinoma

Abstract: Background: Targeted therapy with anti-human epidermal growth factor receptor-2 (HER2) monoclonal antibody in patients with HER2 overexpressed esophagogastric adenocarcinoma (EGA) improves survival; however, the effect is transient due to the development of resistance. Some studies suggest that cMet overexpression provides cross talk for epidermal growth factor receptor (EGFR) and HER2 inhibition. We sought to characterize the expression profile of the EGFR family and cMet receptors in untreated, resected EGA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
3
1
Order By: Relevance
“…However, another study reported a higher VEGF expression rate in tumor and background tissue, as corroborated by our results [17]. Chan et al [18] studied the IHC expression of EGFR, HER-2, and c-MET in patients with EAC and reported a higher expression of these markers than that in our results; however, this study included only patients with early disease and primary surgery. HER-2 has been often studied in esophageal cancer for treatment with trastuzumab [18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, another study reported a higher VEGF expression rate in tumor and background tissue, as corroborated by our results [17]. Chan et al [18] studied the IHC expression of EGFR, HER-2, and c-MET in patients with EAC and reported a higher expression of these markers than that in our results; however, this study included only patients with early disease and primary surgery. HER-2 has been often studied in esophageal cancer for treatment with trastuzumab [18].…”
Section: Discussionsupporting
confidence: 91%
“…Chan et al [18] studied the IHC expression of EGFR, HER-2, and c-MET in patients with EAC and reported a higher expression of these markers than that in our results; however, this study included only patients with early disease and primary surgery. HER-2 has been often studied in esophageal cancer for treatment with trastuzumab [18]. A systematic review of nine studies reported a pooled expression of 25% (146 of 573 patients) for HER-2 in EAC, but this meta-analysis revealed large differences in results between studies [19].…”
Section: Discussioncontrasting
confidence: 63%
“…EGFR signaling can involve a number of intracellular molecules such as extracellular signal-regulated kinase (ERK), cyclin D1 and β-catenin [51]. The presence of EGFR is detected in a wide range of cancer types (Table 3 [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77]). Normally, the EGFR gene is located on chromosome 7.…”
Section: The Egfr and Its Familymentioning
confidence: 99%
“…c-Met staining was scored using a four-step scale: negative (0), weak (1+), moderate (2+), and strong (3+) positivity. If tumor cells stained moderately or strongly positive in more than 30% of tumor cells were considered to be positive [15,16]. The histopathological results were reviewed by two experienced pathologists.…”
Section: Pathologymentioning
confidence: 99%